Healing Fietas : using architecture as a healing catalyst to revive the lost memories of place and space - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2023)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2022.